La religione secondo Marx: “Oppio del popolo” e “coscienza della trascendenza” - Izzo, Francesca (Bollettino Filosofico, 2025)
In recent years there has been a renewed interest in the theme of religion in Marx at an international level. This article documents its centrality and development outside of obsolete dogmatism or forced ideology. The reconstruction of Marx’s itinerary follows the contradictions and turning points that mark his thought from the initial Young Hegelian criticism to Feuerbachism, on the first outline of his historical-materialistic theory in the The German Ideology and finally the theory of fetishism in the Capital. For Marx, overcoming religious alienation is not the outcome of the conflict between philosophy and theology, as atheism proposes. Religion is a necessary mythology which is not dissolved by the enunciation of its illusory nature. Religion persists as long as non-transparent relationships persist between men and between things and men. In the meantime, full religious freedom must be guaranteed and any coercive intervention in the field of consciousness must be rejected. Keywords: Alienation, Fetishism, Philosophy, Ideology, Religion